Influence of Training Method and Running Speed Toward Ball Dribbling Skill Improvement of Soccer Extracurricullar Students of The Whole 02 Cluster of JHS Students in Semarang (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2020)
This research aimed to analyze influences of 40 – Yard sprint training method and 40 –Yard Backpedal – Forward training method to dribbling skill of soccer. The variables of this research consisted of manipulative variables: 40 yard sprint and 40 yard backpedal – forward trainings, independent – attributive variables (the controlled variables): high and low speeds. The sample consisted of whole 02 cluster of JHS soccer extracurricular students in Semarang with total 40 participants. The normality test showed sig score of pretest data 0.2335 > 0.05. Thus, the data was normally distributed. The homogeneity test showed from all indicators of test, the sig score 0.05 ≥ 5%. Thus, H0 was accepted. Therefore, the data was homogeneous. The Two Way Anova test results on the training variables showed sig score 0.017 < 0.050. It meant that there was dribbling speed difference between first and second experimental groups. Dealing with speed as the variable, the sig score = 0.008 < 0.050. It showed that tehre was dribbling speed difference between high speed and low speed respondents. The conclusions were there was influence of 40 – yard sprint and 40 – yard backpedal forward to dribbling skill in soccer of the students, there was influence on high and low speed to dribbling skill in soccer of the students, and there was interaction between the methods to the dribbling skill of the students.